UPAYA PENINGKATAN HASIL BELAJAR SISWA KELAS 5 PADA MATA PELAJARAN IPAS DENGAN MODEL COOPERATIVE TIPE TPS (THINKING PAIR SHARE) MELALUI MEDIA VIDEO INTERAKTIF DI SDN SIRAPAN 01 - Widad Aziza, salwa naila; Erni Trisna Wardani; Erinda Dwi Oktaviani; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the learning outcomes of fifth grade students at SDN Sirapan 01 in the subject of science and natural sciences which are still low. This is due to the use of inappropriate learning models and media. The purpose of this study was to determine the effectiveness of the implementation of the TPS (Think Pair Share) cooperative model assisted by interactive video media on the learning outcomes of fifth grade students at SDN Sirapan 01. This research is a classroom action research using several specific stages, namely planning, implementation, observation and action (reflection). The stages carried out in this cycle take place in similar steps and are carried out 2 times in cycles. The classroom action research carried out with 2 cycles provides a confirmation of the results, that in cycle 1 consisting of 11 students who can be declared complete and 7 have not had learning completeness with a percentage of completeness of 61.11%. While in cycle 2, the learning outcomes of students showed that 18 students were declared complete with a percentage of completeness of 100%. Based on the results of the study, it can be concluded that the use of interactive video media in science learning in class V SDN Sirapan 01 is stated to have increased through the media, where this increase is identified through the development of learning outcomes between cycles 1 to 2 of 38.89%.